Does language influence the vertical representation of auditory pitch and loudness? - Fernández-Prieto, I; Spence, C; Pons, F; Navarra, J (SAGE Publications, 2017)
Sounds that are higher in frequency and louder are associated with higher positions while lower frequency and quieter sounds are associated with lower locations, respectively. In English, "high" and "low" are used to label pitch, loudness and spatial verticality. By contrast, different words are preferentially used, in Catalan and Spanish, for pitch (high: "agut/agudo"; low: "greu/grave") and for loudness/verticality (high: "alt/alto"; low: "baix/bajo"). Thus, English and Catalan/Spanish differ in their spatial connotations of pitch. To analyse the influence of language on these crossmodal associations, we conducted a task in which English and Spanish/Catalan speakers had to judge whether a probe tone was higher or lower (in pitch or loudness) than a reference tone. The response buttons were located at crossmodally congruent or incongruent positions with respect to the probe tone. Crossmodal correspondences were evidenced in both language groups. However, English speakers showed greater effects for pitch, suggesting an influence from the linguistic background.